Socio-Technical Aspects of The Enterprise Transformation In The Conditions of Industry 4.0 - Bartosz JASIŃSKI (Communications of International Proceedings, 2021)
Contemporary enterprises competing in the environment, in the conditions of Industry 4.0, face numerous challenges related to the need to adapt their internal structure to new technical, market and social conditions. The purpose of this article is to characterize the socio-technical aspects of enterprise transformation in Industry 4.0 conditions. The article characterizes the challenges related to Industry 4.0, and based on the H. Leavitt model, their potential impact on the internal organization of the company is presented. Then, based on the analysis of the business case of a Polish service company, conclusions were formulated regarding the directions of the company's transformation in the conditions of Industry 4.0 in the social and technical area.
Keywords: Industry 4.0; transformation of the enterprise; Leavitt Model